Population pharmacokinetic modelling of repaglinide in healthy volunteers by using Non-Parametric Adaptive Grid Algorithm - Ruzilawati, A. B.; Mohd Suhaimi, A. W.; Gan, S. H. (Journal of clinical pharmacy and therapeutics, 2010)
Summary Objective:  To estimate population pharmacokinetic parameters of repaglinide in 121 healthy Malaysian volunteers. Methods:  Each subject received 4 mg of oral repaglinide. Six blood samples were taken per individual (0, 30, 60, 120, 180 and 240 min) for repaglinide’s serum concentration determination by using high‐performance liquid chromatography. The parametric Iterative Two‐Stage Bayesian Population Model (it2b) program followed by the Non‐Parametric Adaptive Grid (npag) program was used to determine a population pharmacokinetic modelling of repaglinide. Results:  Using the npag program, the mean elimination rate constant (kel) of repaglinide was 0·58 ± 0·27 h and the volume of distribution (Vd) was 23·09 ± 9·19 L/h. Conclusion:  In this first report, specifically on the population pharmacokinetic modelling of repaglinide, the data generated should help us to better understand appropriate dosage‐regimens for the drug.